2009
DOI: 10.1038/sj.bjc.6605064
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Wnt/β-catenin signalling pathway induces chemoresistance to interferon-α/5-fluorouracil combination therapy for hepatocellular carcinoma

Abstract: Type I IFN receptor type 2 (IFNAR2) expression correlates significantly with clinical response to interferon (IFN)-a/5-fluorouracil (5-FU) combination therapy for hepatocellular carcinoma (HCC). However, some IFNAR2-positive patients show no response to the therapy. This result suggests the possibility of other factors, which would be responsible for resistance to IFN-a/5-FU therapy. The aim of this study was to examine the mechanism of anti-proliferative effects of IFN-a/5-FU therapy and search for a biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 43 publications
4
77
0
Order By: Relevance
“…Our results obtained by evaluation of cell cycle kinetics revealed that cells with high Smad4 expression were arrested in the G2-M phase under 5-FU treatment, owing to inhibition of the CDC2/cyclin B/survivin cascade. Accumulation of cells in the G1/S phase may result in resistance to 5-FU treatment, which is consistent with previous studies (34)(35)(36). Smad4 reduced the CDC2/cyclin B complex and survivin in both the CT26 and SW620 cells, through the downregulation of the PI3K/Akt pathway, resulting in cell cycle arrest and cell apoptosis.…”
Section: Discussionsupporting
confidence: 80%
“…Our results obtained by evaluation of cell cycle kinetics revealed that cells with high Smad4 expression were arrested in the G2-M phase under 5-FU treatment, owing to inhibition of the CDC2/cyclin B/survivin cascade. Accumulation of cells in the G1/S phase may result in resistance to 5-FU treatment, which is consistent with previous studies (34)(35)(36). Smad4 reduced the CDC2/cyclin B complex and survivin in both the CT26 and SW620 cells, through the downregulation of the PI3K/Akt pathway, resulting in cell cycle arrest and cell apoptosis.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we divided enrolled patients into Ep-CAM high and low-expression group by four of Ep-CAM expression scoring and this cut-off line was based on the previous reports (Gastl et al, 2000;Varga et al, 2004;Fong et al, 2008;Noda et al, 2009). However, as shown in Figure 2, it might not be appropriate to set the cut-off line at four because there were many patients scoring between 4 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry and evaluation of staining For immunohistochemical staining of Ep-CAM expression, we used the method as previously described (Noda et al, 2009). For negative controls, sections were treated the same way except that they were incubated with Tris-buffered saline instead of the primary antibody and normal pancreatic duct epithelium present in each section and Ep-CAM-transfected pancreatic cancer cell lines (MiaPaCa-2 and PSN1) were used as positive controls.…”
Section: Patient Enrollmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inhibition of GSK-3β leads to cell-cycle progression and resistance to apoptosis in other certain  www.cjcrbj.com types of tumors. What is more, emerging evidence indicated that some GSK-3β inhibitors influenced chemotherapy sensitivity [9,10] . Therefore, the function of GSK-3β and clinical application of GSK-3β inhibitors need to be carefully investigated for the potential harmful effects.…”
Section: Introductionmentioning
confidence: 99%